Skeletal muscle wasting with disuse atrophy is multi-dimensional: the response and interaction of myonuclei, satellite cells and signaling pathways - Brooks, Naomi E.; Myburgh, Kathryn H. (Frontiers in Physiology, 2014)
Maintenance of skeletal muscle is essential for health and survival. There are marked losses of skeletal muscle mass as well as strength and physiological function under conditions of low mechanical load, such as space flight, as well as ground based models such as bed rest, immobilisation, disuse and various animal models. Disuse atrophy is caused by mechanical unloading of muscle and this leads to reduced muscle mass without fibre attrition. Skeletal muscle stem cells (satellite cells) and myonuclei are integrally involved in skeletal muscle responses to environmental changes that induce atrophy. Myonuclear domain size is influenced differently in fast and slow twitch muscle, but also by different models of muscle wasting, a factor that is not yet understood. Although the myonuclear domain is 3-dimensional this is rarely considered. Apoptosis as a mechanism for myonuclear loss with atrophy is controversial, whereas cell death of satellite cells has not been considered. Molecular signals such as myostatin/SMAD pathway, MAFbx and MuRF1 E3 ligases of the ubiquitin proteasome pathway and IGF1-AKT-mTOR pathway are 3 distinctly different contributors to skeletal muscle protein adaptation to disuse. Molecular signalling pathways activated in muscle fibres by disuse are rarely considered within satellite cells themselves despite similar exposure to unloading or low mechanical load. These molecular pathways interact with each other during atrophy and also when various interventions are applied that could alleviate atrophy. Re-applying mechanical load is an obvious method to restore muscle mass, however how nutrient supplementation (e.g. amino acids) may further enhance recovery (or reduce atrophy despite unloading or ageing) is currently of great interest. Satellite cells are particularly responsive to myostatin and to growth factors. Recently, the hibernating squirrel has been identified as an innovative model to study resistance to atrophy.